Increased urinary excretion of the epithelial Na channel activator prostasin in patients with primary aldosteronism. Issue 2 (February 2017) - Pizzolo, Francesca; Chiecchi, Laura; Morandini, Francesca; Castagna, Annalisa; Zorzi, Francesco; Zaltron, Chiara; Pattini, Patrizia; Chiariello, Carmela; Salvagno, Gianluca; Olivieri, Oliviero
Abstract : Objectives: Prostasin is a glycosylphosphatidylinositol-anchored serine protease that is released in urine and is involved in epithelial Na channel activation. A direct association between urinary prostasin (u-prostasin) concentration and activation of the aldosterone-driven pathway has been suggested; however, in previous studies on primary aldosteronism, a semiquantitative evaluation, rather than a precise quantification, of prostasin was performed. We aim to investigate if u-prostasin concentrations are higher in patients with primary aldosteronism than in patients with essential hypertension and whether u-prostasin measurements could be a useful marker for diagnosing primary aldosteronism in hypertensive patients. Methods: A total of 62 primary aldosteronism and 56 essential hypertension patients were enrolled. Biochemical and hormonal parameters were measured by applying routine laboratory methods, and u-prostasin levels were assessed by ELISA. Results: Primary aldosteronism patients had higher u-prostasin levels than did essential hypertension patients. Prostasin levels were positively correlated with the aldosterone-to-renin ratio and inversely correlated with plasma K and urinary Na levels. In the highest concentration quartile, u-prostasin levels were associated with a several-fold higher probability of primary aldosteronism diagnosis in hypertensive patients. Receiver operating characteristic curve analysis showed that prostasin was specific but poorly sensitive as a diagnostic marker for primary aldosteronism. Conclusions: The study shows that an elevated u-prostasin concentration in humans is a specific marker for primary aldosteronism, which involves the classical model of epithelial Na channel activation. There was no statistically significant difference in prostasin concentrations among patients with different primary aldosteronism subtypes. Studies with a larger series of patients are necessary to clarify the clinical usefulness of the prostasin assay.